Multicriteria approach for a multisource district heating. - Dénarié, Alice; Calderoni, Marco; Aprile, Marcello (Springer, 2018)
The EU project SmartReFlex - smart and flexible, 100%-renewable district heating and cooling systems for European cities - aims to promote the massive use of renewable sources for heating and cooling in cities through district heating networks. Among the project activities, the analysis of real case studies shows the potential of renewables in district heating systems. AIRU, Italian Association of District Heating, and the Department of Energy of Politecnico di Milano are supporting the promotion of local initiatives for renewable networks in the Emilia Romagna region: the feasibility of a multisource DHC system in Mirandola is assessed and presented in this paper. In Mirandola's district heating and cooling system, natural gas is only one among several possible energy sources: alternative configurations integrating biomass, biogas and solar thermal have been included in the study. The analysis deals with the extension of the network and with the choice of the best new energy source to cover the new heat demand. The use of the multi criteria decision analysis has been applied in order to perform a holistic analysis of possible energy-related choices by considering competing objectives. For instance, the use of biomass is quite controversial: biomass is a renewable, local and a CO2 neutral source, able to reduce greenhouse gas emissions. However, biomass burning can have negative impacts on air quality by producing pollutants such as PM10, BaP, SOx and NOx. This paper presents the multicriteria process applied to plant design, the various alternatives and the criteria used. The result is a combination of natural gas, biogas, solar thermal energy and biomass, which corresponds to the preference of both the utility and municipality.
Keywords: Energieversorgung; Fernwärme; Erneuerbare Energie; Energiemix; Energieplanung; Luftverschmutzung; Nachhaltigkeit; Entscheidungstheorie